Analysis of influence of cavity content on flow pulsations. (January 2019) - Amromin, Eduard L.; Arndt, Roger E.A.
Highlights: Cavity pulsation can substantially depend on this content because of compressibility of gas-liquid mixtures within the cavities. Compressibility is predetermined by the local sound speed that sharply depends on void fraction and pressure within the cavities. This paper provides numerical analysis of the influence of cavity content on pulsations and compares the results with experimental data for a specially designed hydrofoil. Abstract: Assumptions on the cavity content have an insignificant influence on predictions of time-average characteristics of sheet cavitation. However, cavity pulsation can substantially depend on this content because of compressibility of gas-liquid mixtures within the cavities. Compressibility is predetermined by the local sound speed that sharply depends on void fraction and pressure within the cavities. This speed can be indeed very small, whereas used in many CFD solvers definitions of the mixture density as a linear combination of component densities can lead to enormous overestimation of this speed and, as a result, to underestimation of pulsations of cavity volume and of body lift and drag. This paper provides numerical analysis of the influence of cavity content on pulsations and compares the results with experimental data for a specially designed hydrofoil.